Папілярний рак щитоподібної залози у дітей і підлітків України як наслідок аварії на Чорнобильській АЕС - Комісаренко, І. В.; Коваленко, А. Є.; Омельчук, А. В.; Зінич, П. П.; Янчій, І. Р. (Clinical Endocrinology and Endocrine Surgery, 2008)
The authors have conducted an analysis of the results of treatment of a 481 patients of children's and juvenile age with papillary thyroid cancer. Medical records from 310 women and 171 men (F:М ratio = 1.8:1.0) have been analyzed. The median age of patients was 12.8 ± 0.1 years. Papillary thyroid cancer was characterized by high biological malignancy potential, expressed by a short latent period of disease development with high thyroid and lymphatic invasiveness (extrathyroid tumour invasion in 52,4%; regional metastases in 55,0%; distant metastases to lungs in 11,6% of cases). Patients underwent the following operative interventions: thyroidectomy to 162 (33,7%), thyroidectomy with neck dissection to 268 (55,7%), hemithyroidectomy with resection of contralateral lobe in 51 (10,6%). Performance of thyroidectomy reduced the risk of development of disease relapses by 3,2 times, from 2,3% to 0,7% as compared to the organ-saving operations. Thyroidectomy with neck dissection followed by radioiodine ablation and suppressive thyroid hormone therapy is an optimum protocol of treatment of papillary thyroid cancer in children and adolescents. Five-year survival rate was 99,5%.